If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 5 + 7 = 25 Reorder the terms: 5 + 7 + m = 25 Combine like terms: 5 + 7 = 12 12 + m = 25 Solving 12 + m = 25 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + m = 25 + -12 Combine like terms: 12 + -12 = 0 0 + m = 25 + -12 m = 25 + -12 Combine like terms: 25 + -12 = 13 m = 13 Simplifying m = 13
| 5x-1/18=11-x/18 | | 44=4(3x-4) | | 7x-17=5x+5 | | 3cos(2x+30)=1.5 | | 8x-11=-x-38 | | 0.5xn=3 | | 4x-7/3=5x/3 | | x+1.80=12 | | u=x^2y-3y | | 6.00-2.25=0 | | x-7/3=2 | | 1-7x=31+3x | | 2m+7=-9 | | 5(2.25+6)= | | 1/2x-2=-8 | | 3(x*x)=75 | | x/2-2x/3=7 | | 3XSQ=75 | | 9x+81=567 | | 6x-(-49)=181 | | (secx-1)(sec+1)=tan^2x | | 5-12a= | | 2x+3(x+1)=9+2x | | x^3-2x^2-6-3x=0 | | 2a(-8a+3a)=-16a^2+6a^2 | | 5x-4[x-6]=-11 | | 3(x-4)=2x-6-x | | d=2+-4t+-16t^2 | | d=-16t^2-4t+2 | | 7y^2-y-12=0 | | 3z+z=4 | | 3/4m-1/4m=1 |